2010
DOI: 10.1074/jbc.m110.130054
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 2 Is Expressed by Postnatal Hippocampal Neural Progenitors and Modulates Neuronal Commitment

Abstract: The pannexins (Panx1, -2, and -3) are a mammalian family of putative single membrane channels discovered through homology to invertebrate gap junction-forming proteins, the innexins. Because connexin gap junction proteins are known regulators of neural stem and progenitor cell proliferation, migration, and specification, we asked whether pannexins, specifically Panx2, play a similar role in the postnatal hippocampus. We show that Panx2 protein is differentially expressed by multipotential progenitor cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 56 publications
7
113
0
Order By: Relevance
“…In addition, Panx1 has been shown in some cells and tissues to also be concentrated within intracellular compartments. Whether Panx2 localizes well to the plasma membrane remains an area of intense investigation [27][28][29] as well as whether oligomers of different pannexin isoforms form and function in heterotypic combinations. 2,6,9 Vanden Abeele et al presented evidence for Panx1 forming intercellular channels in HEK293 and human prostate cancer epithelial LNCaP cells, 30 but the Panx1 staining in the plasma membrane is more similar to the dispersed pattern observed by several groups than to a canonical gap junction appearance.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In addition, Panx1 has been shown in some cells and tissues to also be concentrated within intracellular compartments. Whether Panx2 localizes well to the plasma membrane remains an area of intense investigation [27][28][29] as well as whether oligomers of different pannexin isoforms form and function in heterotypic combinations. 2,6,9 Vanden Abeele et al presented evidence for Panx1 forming intercellular channels in HEK293 and human prostate cancer epithelial LNCaP cells, 30 but the Panx1 staining in the plasma membrane is more similar to the dispersed pattern observed by several groups than to a canonical gap junction appearance.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…68,69 Recent work also detected expression of a member of the recently discovered pannexin family, Pannexin 2 in postnatal hippocampal neural stem cells with a role in modulating neuronal development. 70 Aquaporin-4, responsible for water and ion homeostasis in the central nervous system, is also expressed in NSCs and plays important roles in the proliferation, survival, migration and neuronal differentiation of adult VZ NSCs via modulation of intracellular Ca 2+ dynamics. 71 Highly selective pharmacological tools are still lacking for these particular large pore-type channels.…”
Section: Involvement Of Other Types Of Channelsmentioning
confidence: 99%
“…8 are transported to the Golgi apparatus for further processing, whereas the fate of Panx2 remains less understood as many studies suggest that Panx2 is often retained in intracellular compartments that likely include the ER. 9,19,38 We have shown that Panx1 and Panx3 follow a classical ER-Golgi secretory pathway in a Sar1-mediated COPII-dependent manner. 39 Once in the Golgi apparatus pannexins can undergo further editing and be modified into complex glycoproteins that are preferentially targeted to the plasma membrane as was evidenced by cell surface biotinylation assays 9 (Figure 4).…”
Section: Protein Secretionmentioning
confidence: 97%
“…One additional post-translational modification has been reported for Panx2 in a study where an ∼80 kDa species expressed in neural progenitor cells was found to be sensitive to hydroxylamine suggesting that Panx2 could be palmitoylated. 19 Further sitedirected mutagenesis studies will be necessary to confirm the palmitoylated status of Panx2, and additional studies are needed to see if either Panx1 or Panx3 is also palmitoylated.…”
Section: Post-translational Modification Of Pannexinsmentioning
confidence: 99%
See 1 more Smart Citation